EGG HATCHING RATES OF BROWN-MARBLED GROUPER, EPINEPHELUS FUSCOGUTTATUS UNDER DIFFERENT LIGHT WAVELENGTHS AND INTENSITIES - Mohammad Seth, Siti Nasihin; Nai, Han Tan; Rosli, Muhammad Khairulanwar; Saad, Shahbudin; Mohammad Noor, Normawaty; Yukinori, Mukai (Malaysian Journal of Science, 2014)
This study was conducted to examine the egg hatching rates of brown-marbled grouper, Epinephelus fuscoguttatus under different light conditions in terms of light wavelengths and intensities. Results of two-way ANOVA showed significant difference for light wavelengths (p<0.05), while light intensities showed no significant difference. There was no interaction between light wavelengths and intensities. Post-hoc Tukey test showed that hatching rates under green light wavelength were significantly higher than white and yellow light wavelengths (p<0.05). When white light 2.7 µmoles/m²/s was set as the control, the hatching ratio of the brownmarbled grouper under green light 2.7 µmoles/m²/s was almost three times higher than the control. The lowest ratio of hatching rates was observed under the white light 13.3 µmoles/m²/s with 70 percent lower ratio of hatching rates than the control light. Eggs hatching under other light conditions mostly showed higher ratios than the control light. ABSTRAK Kajian ini dijalankan untuk mengkaji kadar penetasan telur kerapu harimau, Epinephelus fuscoguttatus di bawah keadaan cahaya yang berbeza dari segi jarak gelombang dan keamatan. Keputusan ANOVA dua hala menunjukkan panjang gelombang cahaya menunjukkan perbezaan yang signifikan (p<0.05), manakala tiada perbezaan yang signifikan bagi keamatan cahaya. Panjang gelombang cahaya dan keamatan cahaya tidak berkaitan antara satu sama lain dalam mempengaruhi penetasan telur ikan kerapu harimau. Keputusan ujian post-hoc Tukey telah menunjukkan kadar penetasan di bawah panjang gelombang cahaya hijau adalah jauh lebih signifikan daripada cahaya putih dan cahaya panjang gelombang kuning (p<0.05). Apabila cahaya putih 2.7 μmol/m²/s ditetapkan sebagai kawalan, nisbah penetasan ikan kerapu harimau di bawah cahaya hijau 2.7 μmol/m²/s adalah hampir tiga kali ganda lebih tinggi daripada kawalan. Nisbah kadar penetasan paling rendah diperhatikan di bawah cahaya putih 13.3 μmol/m²/s, dengan nisbah kadar penetasan 70 peratus lebih rendah daripada kawalan. Telur menetas di bawah keadaan cahaya yang lain kebanyakannya menunjukkan nisbah yang lebih tinggi daripada kawalan. Keywords: Brown-marbled grouper, Epinephelus fuscoguttatus, light wavelengths, light intensities, egg hatching rates